Roles of octopamine and dopamine in appetitive and aversive memory acquisition studied in olfactory conditioning of maxillary palpi extension response in crickets - Matsumoto, Yukihisa; Matsumoto, Chihiro-Sato; Wakuda, Ryo; Ichihara, Saori; Mizunami, Makoto (Frontiers in Behavioral Neuroscience, 2015)
Elucidation of reinforcing mechanisms for associative learning is an important subject in neuroscience. Based on results of our previous pharmacological studies in crickets, we suggested that octopamine and dopamine mediate reward and punishment signals, respectively, in associative learning. In fruit-flies, however, it was concluded that dopamine mediates both appetitive and aversive reinforcement, which differs from our suggestion in crickets. In our previous studies, the effect of conditioning was tested at 30 min after training or later, due to limitations of our experimental procedures, and thus the possibility that octopamine and dopamine were not needed for initial acquisition of learning was not ruled out. In this study we first established a conditioning procedure to enable us to evaluate acquisition performance in crickets. Crickets extended their maxillary palpi and vigorously swung them when they perceived some odors, and we found that crickets that received pairing of an odor with water reward or sodium chloride punishment exhibited an increase or decrease in percentages of maxillary palpi extension responses to the odor. Using this procedure, we found that octopamine and dopamine receptor antagonists impair acquisition of appetitive and aversive learning, respectively. This finding suggests that neurotransmitters mediating appetitive reinforcement differ in crickets and fruit-flies.